An assessment of the physical plant of the Quezon City Science High School - Cabrido, Anacleta Nitura 1929-
Data on the site, buildings and services, facilities and equipment were analyzed in terms of adequacy, manner of utilization, management and maintenance functions. The present school site, which is temporary, is only 2.4 hectares with three pre-fab buildings which can provide homeroom for 15 sections. Classrooms with makeshift partitions are used as an auditorium; there are no permanent laboratory rooms for chemistry and physics. The City School Board, Local School Board, School Cafeteria and school organizations are the sources of funds.